МЕТОДЫ И СРЕДСТВА ИДЕНТИФИКАЦИИ ТЕХНИЧЕСКОГО СОСТОЯНИЯ ПРЯДИЛЬНЫХ МАШИН С ЭЛЕКТРИЧЕСКИМ ПРИВОДОМ - Арипов, Н.М.; Отажонова, М.К. (SCIENCE and SOCIETY, 2025)
The article examines methods for diagnosing the technical condition of textile enterprise technological equipment. The main focus is on identifying and forecasting the state of objects based on metric and statistical methods.